Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3109/09638288.2014.972582
|View full text |Cite
|
Sign up to set email alerts
|

Maternal experiences of caring for an infant with neurological impairment after neonatal encephalopathy in Uganda: a qualitative study

Abstract: Purpose: The study investigated maternal experiences of caring for a child affected by neurological impairment after neonatal encephalopathy (NE) (“birth asphyxia”) in Uganda. Methods: Between September 2011 and October 2012 small group and one-on-one in-depths interviews were conducted with mothers recruited to the ABAaNA study examining outcomes from NE in Mulago hospital, Kampala. Data were analysed thematically with the aid of Nvivo 8 software. Findings: Mothers reported caring for an infant with impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 34 publications
2
26
1
1
Order By: Relevance
“…Moreover, the long term outcomes of children with NDD may be influenced by the severity of the problem, available services and care, caretakers' opinions on causes, as well as their attitudes and resilience in taking care of the children [5,6]. In LICs, caretakers of infants with developmental delays and neurological deficits oftentimes have limited knowledge on the causes of the problem, how it can be managed and the likely future consequences, which may compromise care seeking [3,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the long term outcomes of children with NDD may be influenced by the severity of the problem, available services and care, caretakers' opinions on causes, as well as their attitudes and resilience in taking care of the children [5,6]. In LICs, caretakers of infants with developmental delays and neurological deficits oftentimes have limited knowledge on the causes of the problem, how it can be managed and the likely future consequences, which may compromise care seeking [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, care-seeking practices in LICs for children with NDD remain poorly understood. Earlier studies in Uganda and Malawi evaluated parents' experiences about young children delivered in tertiary hospitals from urban setting [7,11]. In Kenya, a study done in a rural setting, looked at care-givers' experiences of school-going children [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining early neurodevelopmental outcomes after NE revealed a high prevalence of neurodevelopmental impairment (NDI) with 25% of those affected also having malnutrition from related feeding difficulties 15. Qualitative work highlighted the stigma and broad-ranging social, emotional and financial impacts on affected families 3…”
Section: Methodsmentioning
confidence: 99%
“…While in recent decades substantial progress has been made in reducing child mortality in low-income and middle-income countries (LMICs), the global burden of developmental disabilities remains unchanged 2. Child neurodevelopmental impairment (NDI) significantly impacts families in any context, but particularly in low-resource settings, where availability and access to support services are limited, financial barriers greater and social stigma more overt 3…”
Section: Introductionmentioning
confidence: 99%
“…cognitive, physical, visual) that have a long-term influence on their health and development [2]. Families play an important role in care for these children, and caregivers of children with disabilities often experience high levels of stress, anxiety, depression, physical exhaustion, and discrimination [3][4][5][6][7][8]. These experiences contribute to decreased quality of life compared to caregivers of non-disabled children, and may result in reduced effectiveness of parenting [9,10].…”
Section: Introductionmentioning
confidence: 99%